Association of serotype with risk of death due to pneumococcal pneumonia: a meta-analysis - Weinberger, Daniel M; Harboe, Zitta B; Sanders, Elisabeth A M; Ndiritu, Moses; Klugman, Keith P; Rückinger, Simon; Dagan, Ron; Adegbola, Richard; Cutts, Felicity; Johnson, Hope L; O'Brien, Katherine L; Scott, J Anthony; et al. (Clinical infectious diseases, 2010)
The 92 capsular serotypes of Streptococcus pneumoniae differ greatly in nasopharyngeal carriage prevalence, invasiveness, and disease incidence. There has been some debate, though, regarding whether serotype independently affects the outcome of invasive pneumococcal disease (IPD). Published studies have shown variable results with regard to case-fatality ratios for specific serotypes and the role of host factors in affecting these relationships. We evaluated whether risk of death due to IPD is a stable serotype-associated property across studies and then compared the pooled effect estimates with epidemiologic and biological correlates. We performed a systematic review and meta-analysis of serotype-specific disease outcomes for patients with pneumonia and meningitis. Study-specific estimates of risk of death (risk ratio [RR]) were pooled from 9 studies that provided serotype-specific data on pneumonia and meningitis using a random-effects method with serotype 14 as the reference. Pooled RRs were compared with RRs from adults with low comorbidity scores to evaluate potential confounding by host factors. Significant differences were found in the RR estimates among serotypes in patients with bacteremic pneumonia. Overall, serotypes 1, 7F, and 8 were associated with decreased RRs, and serotypes 3, 6A, 6B, 9N, and 19F were associated with increased RRs. Outcomes among meningitis patients did not differ significantly among serotypes. Serotypes with increased RRs had a high carriage prevalence, had low invasiveness, and were more heavily encapsulated in vitro. These results suggest that IPD outcome, like other epidemiologic measures, is a stable serotype-associated property.